PENGARUH MEDIA FLASHCARD BERBASIS METODE GLOBAL TERHADAP KETERAMPILAN MEMBACA KATA SISWA KELAS II SD - Aulia, Dinar; Bahauddin Azmy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of flashcard media based on the Global Method on the word reading skills of second-grade elementary school students. The study was motivated by students’ low word reading ability, particularly in terms of fluency, accuracy, and holistic word recognition. A quantitative approach was employed using a quasi-experimental design with a Nonequivalent Control Group Design. The participants consisted of 46 second-grade students divided into an experimental group and a control group. Data were collected through pre-test and post-test instruments measuring word reading skills. The data were analyzed using normality and homogeneity tests followed by an Independent Samples t-test. The findings revealed that the post-test mean score of the experimental group (88.48) was higher than that of the control group (75.96). the hypothesis testing showed a significance value of 0.000 (< 0.05), indicating a statistically significant effect. Therefore, flashcard media based on the Global Method significantly improves students’ word reading skills, particularly in terms of fluency and accuracy.